COMPARISON OF NADROPARIN 2850 IU AND ENOXAPARIN 4000 IU FOR THROMBOPROPHYLAXIS IN COLORECTAL CANCER SURGERY - Dr. Jerish Murari (Journal of Population Therapeutics and Clinical Pharmacology, 2021)
It is not clear which the optimum regime of treatment dosing should be used to utilize thromboprophylaxis using low-molecular-weight heparins on the high-risk members of the general population. Objectives: The aims of the study shall be to find out the efficacy of the nadroparin 2850 IU (0.3mL) and enoxaparin 4000 IU (40mg) in the prevention of the venous thromboembolism (VTE) developing after colorectal cancer is treated surgically and compare the safety of the two agents of treatment. Patients and Methods: The patients scheduled to be resected where randomized so as to receive single dose therapy of either- 2850 IU nadroparin- or- 4000 IU enoxaparin once a day and within 9 +/- 2 days. The initial safety precaution was major bleed. Advantage was taken of all the results by a blinded independent committee. Results:The effectiveness could be determined in 950 (73.8 percent) of the 1288 patients who were included in the analysis. Nadroparin 15.9 percent (74/464), enoxaparin 12.6 percent (61/486); relative risk 1.27 (95 percent confidence interval; CI: 0.93 1.74) and the result was not inferior to non inferiority of nadroparin. The equality in the proximal DVT event of the groups were 3.2 and 2.9 respectively, whereas it was lower on the sympathetic VTE of the nadroparin side (0.2 and 1.4 respectively). The difference on the other hand was also observed to be significant between the nadroparin and the enoxaparin group in major bleeding both in 7.3 percent in the former and 11.5 percent based on the latter respectively. Conclusion: Nadroparin 2850 IU when compared to 4000 IU Enoxaparin found the greater percentage of the completely asymptomatic distal DVT as well as a smaller percentage of the symptomatic VTE. Nadroparin has been obtained with a risk form of major bleeding which was minimized.